Obtenção de diagramas ternários de biodiesel microemulsionado de óleo de girassol - Cavalcante, José Demétrio Nery (Universidade Federal Rural do Semi-Árido, 2017)
The quest by energy sources has became one of the main interests of the man, causing a enormeous impact on the society. This quest generate a growing on the knowledge, made possible the use of feedstock like energy source. Between of the first feedstock emerge the non-renewable energy sources which are very polluting. As way of searching a solution to the energy sources, the fuels non-polluting, like biodiesel, are presented as an alternative. Starting from this problematic, that work has an objective obtain the ternary diagrams of a microemulsion create starting from a solution of biodiesel, water and a surfactant. The obtaining of the data in laboratory made it possible the construction of the ternary diagrams and your analysis. With the diagrams constructed, we can observe than the surfactants used generate good regions of microemultion.
Keywords: Biodiesel; diagramas ternários; microemulsão; tensoativo; ternary diagrams; microemultion; surfactant; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA